The family of constructivism and the contribution of a pragmatic dimension - Lueg, Klarissa (Proceedings of Pragmatic Constructivism, 2013)
Taking an agent-centred management perspective, this paper reviews several relevant streams of research and theory development in social constructivism in order to investigate the possible link for a pragmatic dimension. Whilst social constructivism and related theories and concepts have been (mis)perceived as either fostering an arbitrary perspective on or assessment of human action or “scepticism, critique and deconstruction” (Søderberg et al. 2002), pragmatic constructivism seems to be the only contemporary theoretical toolset that recognizes both structural constructions and the agents’ capability of action from a management perspective.